Agri-industrial push: Diversifying Nigeria’s economy for stability (2021–2026) - Juliana Onyedika Iwuno; Chibuzo Charles Nwosu; Ifeanyi Ositadinma Onuigbo; Daniel Chimaobim Achinike (Studies in Economy and Public Policy, 2026)
Purpose: This study explores the role of the agri-industrial sector in stabilizing the Nigerian economy, focusing on investment trends, policy frameworks, and rural transformation. Research Methodology: This study employed a mixed-methods approach, combining surveys and key informant interviews across six geopolitical zones to analyze the effects of agri-industrial interventions on GDP growth, employment, and inflation control. Results: The findings suggest that robust investment in agricultural processing and infrastructure is correlated with enhanced economic stability; however, bottlenecks in policy implementation and rural financing persist. The study concludes with pragmatic recommendations for building a resilient post-oil Nigerian economy through modernizing agribusiness. Conclusions: The study concludes that agri-industrialization represents a viable and strategic pathway towards achieving Nigeria’s long-sought economic diversification and post-oil stability. Limitations: Despite significant research on agricultural production and policy in Nigeria, there is a notable lack of longitudinal empirical studies assessing how agri-industrial strategies implemented between 2021 and 2026 contribute to economic diversification and macroeconomic stability. This gap is particularly evident in areas such as value chain integration, governance effectiveness, private sector participation and regional variations. To address this gap, this study employed a comprehensive analysis to link policy implementation with measurable outcomes in economic diversification and stability during the specified period. Contributions: This study offers insights into the framework and strategies that can be adopted in agri-industrialization in Nigeria for the agricultural sector’s transformational and economic stability.